Peranan Hakim dalam Perubahan Sosial Masyarakat - Sutrisno, Sutrisno (Universitas Muhammadiyah Sumatera Barat, 2019)
The judiciary is a system consisting of elements of judges, prosecutors, police, lawyers and correctional institutions. The judge is the last figure expected to realize the values of justice. Judges as agents of change can totally change attitudes and views and patterns of relationships between citizens towards social change through their decisions. Judges are expected to be able to find laws that can be used as social engineering, namely as a tool to change Indonesian society. A judge in the general court environment through his decision must be progressive and have values in a just society. Moral constancy and the attitude and professionalism of a judge must always be attached to each judge.